Efficacy and safety of a Chinese herbal formula Maxing Ganshi Decoction in children with community-acquired pneumonia: A randomized, double-blind, placebo-controlled, multicenter trial - Zheng, Yujiao; Shi, Changren; Han, Yaowei; Li, Xinmin; Dong, Lijing; Li, Yan; Chen, Hui; Wang, Yushui; Li, Jinsong; Liu, Geli; Ma, Rong; Lian, Fengmei; et al. (Frontiers in Pharmacology, 2022)
Background: As one of the most commonly used Chinese medicine formula in the manage of respiratory diseases, Maxing Ganshi Decoction (MGD) has been demonstrated to improve the clinical symptoms of pneumonia. To evaluate the efficacy and safety of MGD in treating children with community-acquired pneumonia (CAP), we conducted the clinical trial. Methods: A randomized, double-blind, placebo-controlled, multicenter trial was conducted in 3 study sites in Tianjin, China. MDG or placebo were randomly given to patients aged 3 to 6 years with onset of CAP within 48 hours. Changes in disease efficacy during the study period (which was measured as recovery, significant effect, improvement and no effect) was evaluated as the primary outcome. Time from enrollment to fever resolution was assessed as the secondary outcome. The adverse event was analyzed as safety evaluation. Results: A total of 71 patients (36 in MGD and 35 in placebo) were randomized and completed the whole study. The patient demographics and other characteristics at baseline were similar between the 2 groups (P > 0.05). After 10 days of intervention, the proportion of recovered and significant effective patients was increased significantly in the MGD group (34.85% [95% CI, 12.44% to 57.26%]; P < 0.05) compared with the control group. Besides, the symptom score of the MGD group was lowered significantly (P < 0.001). The estimated time to fever resolution in the MGD group was also reduced compared with the control group (P < 0.05). During the whole study, no side effects were observed in both MGD and control groups. Conclusions: MGD was effective in improving disease efficacy, clinical symptoms and reducing time to fever resolution in patients with childhood CAP, which suggested that MGD may be used as an alternative therapy in in the treatment of childhood CAP. TRIAL REGSITRATION. ChiCTR-TRC-12002991.